Long-term aripiprazole effectiveness in bipolar disorder patients decreases with pharmacotherapeutic complexity and degree of baseline mood disturbance - Pichai Ittasakul (2018)
Background: Aripiprazole, a second-generation antipsychotic, has been shown to have short-And long term efficacy in bipolar disorder as monotherapy and in two-drug combinations. However, its long-term effectiveness among patients with different degrees of pharmacotherapeutic complexity and baseline mood disturbances is not known.Objective: To assess long-term aripiprazole effectiveness in bipolar disorder (BD) patients in relationship to pharmacotherapeutic complexity and degree of baseline mood disturbance.Methods: Outpatients assessed with the Systematic Treatment Enhancement Program for BD (STEP-BD)Affective Disorders Evaluation, and monitored with the STEP-BD Clinical Monitoring Form received open-label aripiprazole.Results: Ninety-seven patients (52 BDI, 40 BDII, 5 BD NOS, mean age 40.2 years, 75.3% female) received aripiprazole combined with a mean ± SD (median) of 2.9 ± 1.7 (3) other prescription psychotropics, with 39.2%(38/97) receiving up to triple-pharmacotherapy (aripiprazole plus up to 2 other psychotropics) and 60.8% (59/97)taking quadruple-or-more-pharmacotherapy (aripiprazole plus at least 3 other psychotropics). At baseline 71.1% (69/97) of patients were symptomatic and 28.9% (28/97) were euthymic. Overall, mean (median) aripiprazole final dose and duration were 17.6 (15) mg/day and 388 (190) days, respectively. Aripiprazole was discontinued in only one-quarter of euthymic patients taking up to triple-pharmacotherapy, but in two-thirds of other patients(symptomatic patients taking up to triple-pharmacotherapy and symptomatic/euthymic patients taking quadrupleor-more-pharmacotherapy).Conclusion: Aripiprazole treatment of bipolar disorder may be modestly extended beyond mono-pharmacotherapy and dual-pharmacotherapy to include triple-pharmacotherapy in euthymic patients, but further extension beyond current indications may not be effective in most patients.